How does the media contribute to the rise of hate crimes against foreign domestic helpers in Hong Kong? An unfair problem frame and agenda setting - Chen, Zhuoli (Frontiers in Sociology, 2024)
Hate crimes are widespread in Hong Kong society. Foreign domestic helpers working in Hong Kong also experience unfair agenda-setting by the media due to their dual economic and social disadvantages, and the media tries to portray them in a hostile social role. At the same time, the media creates negative social images of minority groups through news coverage, which leads to an increase in social hate crimes against them. This study used WiseSearch, a Chinese newspaper collection and analysis platform, to explore how Hong Kong news media use news themes and content to create a negative image of Hong Kong foreign domestic helpers in order to understand the media origins of hate crimes against Hong Kong foreign domestic helpers. Ultimately, the study found that local news media in Hong Kong are more inclined to cover the legal disputes of foreign domestic helpers in the agenda-setting process. In addition, they are more likely to associate foreign domestic helpers with "fear" rather than "rest assured." The study also found that because of the news value orientation, Hong Kong media tended to treat foreign domestic helpers as outsiders and less sympathetically when writing news stories.